Analisis Tegangan Akibat Pembebanan Statis pada Desain Carbody Tec Railbus dengan Metode Elemen Hingga - Sutikno, Endi (Jurnal Rekayasa Mesin, 2011)
Railbus is one type of vehicle operated for a short distance. Although that operated on the rail, construction rail bus more likely to match construction with small size busses and passengers abit becouse the porpuse of use that speed is faster than regular train, railbus which has several different design of the produc of the PT KIA previusly requere the precence of the force to be know sequrity testing products to be produced, railbus should be able to accept the burden of both passenger as well as from its own weight, including load time of the coupling between the carriages.Research conducted at carbody TeC railbus in the three different loading cases, namely case 1, which stimulated loading occuring at the time railbus carbody TeC is in the push condition, case 2 represents the state loading on the carbody TeC railbus during compression on the other locomotive on the coupling process railbus done to connect with other locomotives, and case 3 which represents the state loading carbody TeC railbus when withdrawal of the oher locomotives when railbus not operated of a simulation, and the known distribution of the stress that occurs in TeC railbus carbody construction design on static loading distribution and the result of the stress that occurs in all three cases, ie the largest stress value in the first case occured in an area with a stress value frontpart 157,883Mpa, in the second case occured in an area frontpart with a stress value of 193,033Mpa, and the thirdcase, a stress of 140,615Mpa occurs in area crossbeam of the underframe. The third stress occurs in all three cases remained at the limit of material strength, so it can inferred TeC railbus carbody construction design is consider capable receiving a load that will be accepted railbus during operation.Keywords : Stress Analysis, Railbus, Finite Elemen Method